Knowledge sharing among business service professional in Malaysia: An exploratory study - Mohd Misron Omar; Noor Raihan AB Hamid (Proceedings of AICS - Social Sciences, 2017)
Knowledge sharing plays an important role in the domain of business services. It leads to knowledge creation and decision making among its business professional. Although Knowledge Sharing Behaviour (KSB) among other professionals is acknowledged as important by scholars, understanding of what influence this behaviour among the business professional remains limited especially from Malaysia’s Business perspective. The Malaysian Government announced six Strategic Reform Initiatives (SRIs), the second critical component of the Economic Transformation Programme (ETP) in addition to the 12 National Key Economic Areas (NKEAs), to boost Malaysia’s global competitiveness. The ETP was conceptualized with two key thrusts of focus, through the 12 NKEAs and competitiveness, to be delivered by the SRIs. The Human Capital Development (HCD) is one of the SRIs while Business Services are one of the 12 NKEAs. For this reason, the professional workings in business services of NKEAs were surveyed using the online web survey for this exploratory study. In this exploratory study, The Theory of Planned behaviour (TPB) was applied as the theoretical backbone of the conceptual framework. Understanding the determinants of this behaviour is important as it helps to encourage sharing of knowledge among business services professional community and should be an interest to academics and human capital development practitioners in this domain.